Efektivitas Metode Afirmasi Dalam Mereduksi Kecemasan Pada Penderita Kanker Leher Rahim - Rahayu, Veronika Rika; Pramadi, Andrian (Faculty of Psychology, Universitas Surabaya, 2005)
In today's global economy, many products designed by European companies are sold worldwide. These products are used by different user groups in the world with different cultures who think and behave indifferent ways. Cross-cultural usability testing provides the key in defining the cultural differences in product usage and user needs between user groups. In this research, a cross-cultural usability testing of a European product is conducted between Dutch and Indonesian user groups by means of observation and interview. The participants are observed individually on how they use the product, what problems they experienced in using the product and their behavior in using the product and solving the problems they encountered. The usability testing is carried out using the think-aloud' method during the observation, which means that the participants are asked to speak about what they are doing and thinking when using the product. Comparing the results found, it can be concluded that Dutch and Indonesians use and perceive a product in a different way. The findings suggest that cross-cultural usability testing may be very useful when designing products for users with different cultures. It provides a competitive advantage for the companies when entering an international market to ensure equally usable products in different cultures. Efektivitas metode afirmasi dalam mereduksi kecemasan penderita kanker leher Rahim diuji melalui penelitian dengan desain one sample pre-test post-test. Subjek (N=2) adalah penderita kanker leher rahim stadium 2, dikenai perlakuan berupametode afirmasi, dua kali sehari, selama dua minggu. Data yang diperoleh diolah dengan analisisnon-parametrik Wilcoxon. Hasil-hasil menunjukkan metode afirmatif kurang efektif untuk mereduksi tingkat kecemasan penderita kanker leher rahim, terutama pada kondisi yang tidak dapat dikendalikan individu, sertisikap dan dukungan suami, keluarga, dan masyarakat. Disarankan metode afimasi dikenakan pada objek kecemasan yang secara langsung berkaitan dengan diri individu, seperti kecemasan terhadap kematian.